Optimización del proceso de hidrólisis enzimática en la producción de vodka a partir de papa pituca (Colocasia esculenta) Iquitos 2024 - Calle Lozano, Carlos Cristian (2025)
The research presented here focuses on the production of vodka from papa pituca (Colocasia esculenta), a variety with great potential in the alcoholic beverage industry. The main objective was to produce vodka by enzymatic hydrolysis of starch using alpha-amylase and glucoamylase enzymes, in order to obtain a sweetened must suitable for fermentation and subsequent distillation. The research was carried out with a descriptive and experimental 2² factorial design, including a total of 12 experiments to determine the optimal hydrolysis conditions. Starch was extracted from the potato, followed by the evaluation of enzymatic hydrolysis, where the best conditions were found in trial 4, with 1 g of enzymes (1:1 ratio) and a pH of 7, reaching a maximum of 12.7° Brix. Fermentation was carried out with Saccharomyces cerevisiae for seven days, resulting in a vodka production of 280.7 mL with an ethanol content of 40°GL. The quality of the final product met the established standards, with no detectable levels of undesirable compounds. In conclusion, the study demonstrates that the optimisation of enzymatic hydrolysis conditions is crucial to improve the production of vodka from papa pituca, highlighting its potential in the alcoholic beverage industry.